La inversión pública y el gasto público efectuado por el Gobierno Regional de Loreto en el departamento de Loreto, periodo 2018 – 2022 - Tacanga Aspajo, Tiffany Nicole (2024)
The funds allocated each year to the Regional Government of Loreto are limited, so if you dedicate most of them to investment then the amount allocated to spending must decrease, and vice versa. This thesis aims to determine the relationship between public investment and public spending carried out by the Regional Government of Loreto in the department of Loreto, during the period 2018 - 2022. This research is classified as Quantitative, with Correlational explanation and designed as No Experimental. The conclusions reached are that public investment is not directly related to public spending of the Regional Government of Loreto, during the period 2018 - 2022, since the Correlation Coefficient is r = 0.987116857; thereby demonstrating the direct relationship of the variables; and, additionally, the Coefficient of Determination is R2 = 0.974399690; that shows the determination between them. The institution's public investment is concentrated in the economic function Transportation since 33.46% was dedicated to it, amounting to S/. 782.60 million, and was intended to finance the construction of roads, communal roads, access roads in rural areas, among others. Public spending was used to finance the Personal and Obligation concept, allocating 54.40% of the total, equivalent to S/. 5,926.20 million. Public spending was much higher than investment in S/. 10,893.60 million.